Everolimus following 5-aza-2-deoxycytidine is a promising therapy in paclitaxel-resistant clear cell carcinoma of the ovary - Ho, Chih-Ming (Am J Cancer Res, 2018)
Our previous study showed that 5-aza-2-deoxycytidine (5-aza-dC) could inhibit tumor growth by enhancing the susceptibility of ovarian clear cell carcinoma (OCCC) to paclitaxel through decreasing AKT/mTOR expressions. The objective of the study is to evaluate the antitumor efficacy of everolimus (RAD001) and 5-aza-2-deoxycytidine (5-aza-dC) by targeting AKT/mTOR and EZH2 in OCCC. Paclitaxel-sensitive and resistant OCCC cell lines were established. In vitro proliferative and apoptotic assays and flow cytometry were performed. The expressions of EZH2, PIK3IP1, phospho-AKT, phospho-mTOR and phospho-Rictor in the OCCC cell lines were evaluated by Western blotting. In vivo animal experiments with RAD001 and 5-aza-dC were performed. RAD001 alone showed significant in vitro antitumor activity and inhibited in vivo tumor growth in paclitaxel-sensitive and resistant OCCC cells. In addition, 5-aza-dC enhanced the antitumor effects when combined with paclitaxel or RAD001 in both paclitaxel-sensitive and resistant tumors. Activation of phospho-AKT ser473 and PIK3IP1 was observed in RAD001-treated paclitaxel-sensitive and resistant OCCC cells. In contrast, inhibition of phospho-AKT ser473 and EZH2 was observed with RAD001 following 5-aza-dC treatment of paclitaxel-sensitive and resistant OCCC cells. Furthermore, RAD001 following 5-aza-dC enhanced apoptosis of paclitaxel-sensitive and resistant OCCC cells. RAD001 following 5-aza-dC may be a promising treatment strategy for the treatment of both chemo-sensitive and resistant OCCC. Further clinical studies are warranted.